The Difference Between The Use Of Combination Injection Contraception And Medroxyprogesterone Acetate (Dmpa) Contraception With Changes In Body Weight At Tpmb Sri Haryati - Haryati, Sri; Rahmadiyanti, Rahmadiyanti (CV. Inara, 2024)
Background: Combined injectable contraceptives contain the hormones estrogen and progestin, while DMPA contraceptives only contain progestin. This difference can affect the response of the tube to the contraception. Purpose of Writing: to determine the difference between the use of combined injection contraception and medroxyprogesterone acetate (DMPA) contraception with changes in body weight in TPMB Sri Haryati. Research Methods: The method in this study was an experimental design (quasi experiment) with a two group pretest posttest design. In this study, there were divided into two groups, namely the group using combined injection contraception and the group using the medroxyprogesterone acetate contraception (DMPA). Research Results The results of the independent test sample test obtained Asymp. Sig (2 – Sided) has a value of 0.946, because 0.946 > 0.05, the hypothesis is rejected. This means that there is no difference between combination injections and DPMA injections on weight changes before and after the use of combination injections and DPMA injections. Conclusions and Suggestions: The results of this study are expected that midwives can provide health education about family planning using injections in providing counseling both combination and DPMA have a risk of weight gain.